Equity in adjuvant radiotherapy utilization in locally advanced head and neck cancer: A SEER‐data based study. Issue 4 (16th February 2023) - Beckett, Matthew; Gaudet, Marc; Bourque, Jean‐Marc; Dennis, Kristopher; Abdel‐Wahab, May
Abstract: Background: Not all patients with locally advanced head and neck cancer (HNC) who are eligible for adjuvant radiotherapy (RT) following upfront surgery appear to receive it. Methods: Data were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Selected patients from 2009 to 2018 had locally advanced HNC, underwent upfront surgery, and were eligible for adjuvant RT. Multivariable logistic regression and chi‐squared test were used to analyze available patient and tumor characteristics. Results: Of 12 549 patients, 84.5% underwent adjuvant RT, 15.5% did not. Characteristics associated with lowest adjuvant RT utilization included cancers of the larynx ( p  < 0.0001) and gingivae ( p  < 0.0001), age 80 and above ( p  < 0.0001), unpartnered status ( p  < 0.0001), and residence within a nonmetropolitan area ( p  < 0.0024). Conclusions: Tumor subsite, age, partnered status, and rural/urban residence correlate with omission of adjuvant RT in locally advanced HNC.